Dendritic cell-based cancer immunotherapy for colorectal cancer - Kajihara, Mikio (World J Gastroenterol, 2016)
Colorectal cancer (CRC) is one of the most common cancers and a leading cause of cancer-related mortality worldwide. Although systemic therapy is the standard care for patients with recurrent or metastatic CRC, the prognosis is extremely poor. The optimal sequence of therapy remains unknown. Therefore, alternative strategies, such as immunotherapy, are needed for patients with advanced CRC. This review summarizes evidence from dendritic cell-based cancer immunotherapy strategies that are currently in clinical trials. In addition, we discuss the possibility of antitumor immune responses through immunoinhibitory PD-1/PD-L1 pathway blockade in CRC patients.